PENYULUHAN PENCEGAHAN PELECEHAN DAN KEKERASAN SEKSUAL PADA REMAJA DI SMAN 2 TAPUNG HILIR KAMPAR - Salim, Agus; Yuliana, Anastasya Shinta; Fauzi, Dwina Tetiany (Awal Bros Journal of Community Development, 2023)
Sexual harassment and violence are the same as other criminal acts, which also have serious consequences. One of the impacts of sexual harassment and violence is that victims experience emotional suffering, depression, insomnia, inability to focus, and experience decreased interest in studying at school, lower school grades and even drop out of class. As times progress, the thinking of the next generation of the nation changes, today's young people tend to like showing off and exposing parts of their bodies which invites people to commit sexual harassment. Children don't know what to do if something dangerous happens to them. Therefore, the author conducted outreach and distributed posters to prevent sexual harassment and violence against teenagers at SMAN 2 Tapung Hilir. The aim of the education and distribution of posters is so that teenagers know which parts of the body should not be touched and seen by strangers, do not follow strangers and shout for help and report if there are people who want to do evil to them